Disseminated Coccidioidomycosis Following COVID-19 Mimicking Metastatic Thoracic Relapse of Well-Differentiated Liposarcoma: A Case Report - Nassif, Elise F.; Maloney, Nolan; Conley, Anthony P.; Keung, Emily Z. (Frontiers in Medicine, 2021)
Introduction: COVID-19 is associated with immune dysregulation which may increase susceptibility to atypical infectious diseases, particularly in the vulnerable cancer patient population. Coccidioidomycosis is an endemic fungal infection which presents with mild-to-moderate pneumonia in most cases. Case presentation: The presented case is a 67-year-old woman living in the southwestern United States who is under close observation for well-differentiated liposarcoma of the abdominal wall. She presented with persistent cough and fatigue following COVID-19 infection. Imaging revealed new pulmonary nodules, a chest wall mass and bone lesions. The imaging appearance of these lesions was consistent with metastatic disease, although distant metastasis is not typical in well-differentiated liposarcoma. Biopsy of the chest wall mass revealed granulomatous fungal infection and serology was positive for coccidioidomycosis. At the time of diagnosis, the patient was lymphopenic, possibly a sequela of recent COVID-19 infection and which may have contributed to the development of her atypical disseminated form of coccidioidomycosis. Patient was treated with fluconazole for the coccidioidomycosis and continued observation for mild progression of the liposarcoma. On follow-up imaging, the chest wall mass and lung nodules have decreased in size and the patient remains on antifungal treatment. There has been no further increase in the liposarcoma mass. Conclusion: COVID-19 may be associated with increased risk of atypical forms of infectious diseases in cancer patients, which physicians should be aware of before giving systemic treatments for cancer. In endemic regions, co-infection by coccidioidomycosis should be suspected in cases of persistent symptoms after COVID-19 infection.